LEGAL PROTECTION FOR THE OBLIGEE CAUSED BY FAKE PERFORMANCE BONDS (LEGAL CONSTRUCTION TO DISPUTE SETTLEMENT IN CONSTRUCTION LAW) - Octaviani Cristiani Purnama Sari (Universitas Muhammadiyah Ponorogo, 2018)
In a development project activity, financing is a very significant thing. Therefore, in all its activities required a smooth transaction in terms of financing, because without it will certainly be many obstacles that will be experienced by the owners of the project. To avoid this, project owners often involve third parties to ensure liquidity of funds. In order to guarantee this, project owners often use the services of banking institutions. The provisions contained in Law No. 2 of 2017 concerning Construction Services (hereinafter referred to as Construction Services Law) in Article 57 paragraph (1) provides that: